Boon or Burden? The Effect of Private Sector Debt on the Risk of Sovereign Default in Developing Countries - Oya Celasun; Philipp Harms (Verein für Socialpolitik, Ausschuss für Entwicklungsländer, 2008)
We explore how the share of the private sector in total external debt affects perceived creditworthiness and the likelihood of sovereign default in developing countries. While there are theoretical arguments both in favor and against a stabilizing role of private-sector borrowing, the evidence clearly supports the notion that a greater share of the private sector in total external debt is associated with a reduced likelihood of sovereign default.
Keywords: F34; O16; 330; International Investment; Sovereign Risk